Effect of Phyllanthus polyphyllus extract on DNA binding studies - Swapna G; Bharathi K; Rajkapoor B; KVSRG Prasad (International Journal of Phytomedicine, 2014)
Phyllanthus polyphyllus has demonstrated potent in vitro anticancer activity against various tumor cell lines. For a better understanding of the mechanism of action, binding studies of methanolic extract of Phyllanthus polyphyllus (PP) with Calf Thymus (CT) DNA were studied using absorption spectroscopy, viscometry and cyclic voltammetry. PP displayed binding properties to the CT-DNA and was found to interact with CT-DNA through intercalation, as demonstrated by a hypochromic effect and blue-shift in the UV spectra. An increase in the viscosity of CT-DNA was observed. The changes in the current and potential in cyclic voltammetric experiments demonstrate intercalative interaction between the PP and the CT-DNA.